Misuse of prescription opioid analgesics among adolescents in Greece: The importance of peer use and past prescriptions. (October 2014) - Fotiou, Anastasios; Kanavou, Eleftheria; Richardson, Clive; Ploumpidis, Dimitrios; Kokkevi, Anna
<x xml:space="preserve">Abstract</x> Aims: The study explored the prevalence and correlates of the non-prescribed use (misuse) of prescription opioid analgesics in a nationally representative sample of adolescent students in Greece. Methods: Cross-sectional data were collected through anonymous questionnaires administered to a random stratified sample of 676 high schools involving 23, 279 students aged 15–19 in 2011. Findings: About 16.2% reported lifetime misuse, 6.3% repeated misuse at least three times – most of them to alleviate pain. Results of multivariate logistic regression showed that among the strongest correlates of repeated misuse were peer misuse (Odds ratio [OR] = 4.10, 99% Confidence Interval [CI] = 3.11–5.42), past prescription of opioid analgesics (OR = 3.19, 99% CI = 2.28–4.48 in males, OR = 2.38, 99% CI = 1.78–3.19 in females), lifetime misuse of tranquilisers/sedatives (OR = 3.16, 99% CI = 2.22–4.48), and frequent use of over-the-counter analgesics (OR = 2.37, 99% CI = 1.92–2.92). Other correlates included: female gender, daily smoking (by girls), frequent alcohol use, antisocial behaviour, physical or emotional maltreatment, and past prescription of tranquilisers/sedatives. Illicit drug use failed to explain opioid analgesics misuse. Conclusions: Misuse of prescription analgesics is common among adolescents in Greece and seems to emerge within a self-treating rather than a mood-altering context of use.